Justice Scalia : rhetoric and the rule of law - Slocum, Brian G.; Mootz, Francis J., III (Chicago : The University of Chicago Press, 2019)
This work offers a novel collection of interrelated and interdisciplinary essays by a diverse and impressive group of scholars that discuss the rhetoric of the late Justice Antonin Scalia as it relates to the rule of law.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 22, 2019).
Keywords: Scalia, Antonin, -- 1936-2016.; Law -- Interpretation and construction; Constitutional law -- United States -- Interpretation and construction; Rhetoric; Law; Laws of specific jurisdictions & specific areas of law